2016
DOI: 10.1037/pac0000159
|View full text |Cite
|
Sign up to set email alerts
|

Trusting the enemy—Towards a comprehensive understanding of trust in intergroup conflict.

Abstract: Intuitively, we have an implicit understanding of trust, yet when trying to describe the concept, it becomes clear that trust is complex and elusive. Although it is widely recognized that a lack of trust propels groups toward conflict and prevents them from reaching a settlement, there is currently no shared understanding of what shapes trust in intergroup conflict. Further, even though scholars widely acknowledge trust's multidimensional nature, there is no shared understanding on which dimensions exactly con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 15 publications
0
27
0
Order By: Relevance
“…Trust in the outgroup is based, among other dimensions, on their perceived integrity. Thus, the perception that the others are lacking integrity and not acting in accordance with a moral code undermines any fragile trust between groups (Kappmeier, 2016;Mayer, Davis, & Schoorman, 1995).…”
Section: Potential Challenges Destabilizing the Cycle Of Cold Warmentioning
confidence: 99%
See 2 more Smart Citations
“…Trust in the outgroup is based, among other dimensions, on their perceived integrity. Thus, the perception that the others are lacking integrity and not acting in accordance with a moral code undermines any fragile trust between groups (Kappmeier, 2016;Mayer, Davis, & Schoorman, 1995).…”
Section: Potential Challenges Destabilizing the Cycle Of Cold Warmentioning
confidence: 99%
“…By de-legitimizing the account of the others, groups and their members can avoid strong unpleasant emotions such as guilt and shame when they are forcefully reminded of wrong-doing iii . However, a lack of empathy, manifest by their de-legitimization, is a key driver that undermines trust (Kappmeier, 2016(Kappmeier, , 2017Mayer et al, 1995).…”
Section: Potential Challenges Destabilizing the Cycle Of Cold Warmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research identified seven superordinate dimensions, three relating specifically to perception of the outgroup (competence, integrity, predictability) and three to perception of in group and outgroup relations (compassion, compatibility, collaboration) with one further dimension undergirding the others (security). 48 The six dimensions have subthemes while security refers to the perception that the outgroup is not a threat to the physical and psychological safety or identity of the in group. 49 We would argue that security refers not only to the absent of threat, but positive peace that promotes community psychosocial health.…”
Section: Being Muslim Being Scottish Created Trust and Allowed For Homentioning
confidence: 99%
“…Positive expressions of empathy toward an adversary will have positive effects on reconciliation in the presence of a basic level of trust in the outgroup (Nadler and Liviatan, 2006) whereas distrust and lack of empathy both propel groups into conflict (Kappmeier, 2016) and form a formidable obstacle to reconciliation between two conflict groups (Kelman, 2005). In addition, major events related to conflict such as terrorist attacks, wars, and confrontations frequently provide negative information about the adversary which leads to greater perceptions of threat, radicalization of attitudes and less willingness for reconciliation and peace negotiations (Bar-Tal et al, 2006).…”
Section: Emotional and Attitudinal Responses To Terrorism Broadcastsmentioning
confidence: 99%